2013
DOI: 10.3389/fnhum.2013.00474
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Microvascular Specificity of the 3- and 7-T BOLD Response Using ICA and Susceptibility-Weighted Imaging

Abstract: In functional MRI it is desirable for the blood-oxygenation level dependent (BOLD) signal to be localized to the tissue containing activated neurons rather than the veins draining that tissue. This study addresses the dependence of the specificity of the BOLD signal – the relative contribution of the BOLD signal arising from tissue compared to venous vessels – on magnetic field strength. To date, studies of specificity have been based on models or indirect measures of BOLD sensitivity such as signal to noise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(41 reference statements)
0
11
0
2
Order By: Relevance
“…Therefore, as the field is increased, the weighting of T2 contrast increases relative to T2* weighted contrast, with the result that in fields of 4T and higher BOLD contrast is more localized to tissue than to the larger veins when SE acquisitions are employed (Yacoub, Shmuel et al 2001). By contrast, with GRE acquisitions at 7T the T2* of veins is so short the venous contribution becomes small and diffusion weighting from tissue microstructure dominates (Geissler, Fischmeister et al 2013). Because of this, SE acquisitions are to be preferred at 7T, although SE methods have higher RF power deposition (Specific Absorption Rate, SAR), which may reduce the number of slices that can be collected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as the field is increased, the weighting of T2 contrast increases relative to T2* weighted contrast, with the result that in fields of 4T and higher BOLD contrast is more localized to tissue than to the larger veins when SE acquisitions are employed (Yacoub, Shmuel et al 2001). By contrast, with GRE acquisitions at 7T the T2* of veins is so short the venous contribution becomes small and diffusion weighting from tissue microstructure dominates (Geissler, Fischmeister et al 2013). Because of this, SE acquisitions are to be preferred at 7T, although SE methods have higher RF power deposition (Specific Absorption Rate, SAR), which may reduce the number of slices that can be collected.…”
Section: Introductionmentioning
confidence: 99%
“…All fMRI images were acquired using 2D gradient echo‐echo planar imaging (GE‐EPI) with multiband and parallel imaging acceleration (Siemens Healthcare prototype research sequence) with the following acquisition parameters: bandwidth = 1980 Hz/pixel; TE = 30 ms; TR = 500 ms; echo spacing = 0.67 ms; EPI factor = 148; phase encoding shift factor = 2; voxel volume = 1.5 × 1.5 × 1.5 mm 3 ; in‐plane field of view (FOV) = 224 × 224 mm 2 ; FA = 38°, where T 1 = 2,000 ms; partial Fourier = 6/8; acquisition direction = A‐P; multiband factor = 3; GRAPPA factor = 3; number of slices = 21; slice FOV = 31.5 mm. Although minimum TE was 15 ms, 30 ms was chosen based on previous studies where the physiological/thermal noise ratio (Triantafyllou et al, , figure b), t value and percent signal change (% S Δ) were shown to peak at ∼30 ms (van der Zwaag et al, , figure b,c, respectively) and also to reduce the contribution of BOLD signals arising from distant macrovascular veins (Geißler, et al, ; Kennerley, Mayhew, Redgrave, & Berwick, ).…”
Section: Methodsmentioning
confidence: 99%
“…Burada da süreyi kısaltmak için hızlı SE sekansları (HASTE, TSE gibi) kullanılabilir. T2 verilerinin ve BOLD sinyallerinin kaçırılmaması ve nöropsikolojik çalışmalarda 1.5 T cihazlar yetersiz kalmaktadır [11]. Bütün bu veri toplama araçlarını verimli bir şekilde kullandıkta sonra, BOLD sinyalinin çok küçük bir veri olmasından dolayı; istatistiksel analiz için yine de veriyi gürültüden arındırmak ve düzeltmeler yapmak gereklidir [12].…”
Section: Fizik Temelleriunclassified
“…Günümüzde araştırmaların %56'sı 3 ve üzeri Teslaya sahip cihazlar ile yapılmaktadır. Yüksek manyetik alan gücü görüntüyü netleştirmemize ve veri kalitesini artırmamıza yardımcı olduğu gibi negatif ve pozitif data miktarını da aynı oranda arttırarak daha fazla gürültüye neden olmaktadır [11]. [13].…”
Section: Fizik Temelleriunclassified